Computer Availability. (Education Digest, 1982)
This article presents the results of a survey conducted by the U.S. National Center for Education Statistics, according to which the number of personal microcomputers available for instructional use by public school students has tripled between the fall of 1980 and the spring of 1982. The number of computer terminals--those connected with mainframe computers--available for instructional purposes remained almost constant during the same two-year period. Students were found to have access to 96,000 microcomputers and 24,000 computer terminals in the spring of 1982, compared to 31,000 microcomputers and 22,000 terminals in the fall of 1980.